Cloud-Based IoT Air Quality Monitoring System - Kadir A.D.I.A.; Alias M.R.N.M.; Dzaki D.R.M.; Din N.M.; Deros S.N.M.; Haron M.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Air quality; Deterioration; Electric batteries; Indoor air pollution; Monitoring; Testbeds; Volatile organic compounds; Web services; Battery life; Bme680; Cloud-based; ESP32; Indoor air quality; Indoor air quality monitoring; Influxdb; Quality monitoring system; Temperature and humidities; Total volatile organic compounds; Internet of things